PROJECT MANAGER SKILLS, RISK MANAGEMENT TOOLS - Iacob, Vladut (Studies and Scientific Researches. Economics Edition, 2013)
Although the projects are different from each other there are many common things that contribute to their success. Looked overall, the success of a project is the result of a multitude of factors. This person is considered the "engine" of the project. The man who makes the action set for the achievement of project objectives to be brought to an end. The project manager must have the technical knowledge and economic diverse. He should be able to choose a team and lead. You must be tenacious, combative, to know how to communicate both within the team and beyond. In a word, the project manager must have an impressive stock of knowledge, skills and abilities and appreciate as Peter Drucker, to "exist for the organization. To be its servant. Any management who forget this will only cause damage to the organization. "This study will focus on highlighting the skills of the project manager and their role in managing difficult situations or risk.